Interferensi Bahasa Bima Dalam Komunikasi Bahasa Indonesia di Kelas IX SMPN 1 Sape Kabupaten Bima - Arifuddin, Arifuddin (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2019)
This research concerns with the interference of Bimanese language to Indonesian language communicated by the third grade students of SMPN I Sape Kabupaten Bima. The data is oral language which is spoken by the students and teachers whose their mother language is Bimanese. The result of the research shows that there are three types of the interference which are occurred school: phonological, morphological, semantic and syintax interferences. The interference of Bimanese is not occurred consciously, but it is occurred because there is an effect from daily life so that the element of Bimanese words or sentences is still carried in the communication at the school.